Endogenous generation of hydrogen sulfide and its regulation in Shewanella oneidensis - Wu, Genfu; Li, Ning; Mao, Yinting; Zhou, Guangqi; Gao, Haichun (Frontiers in Microbiology, 2015)
Hydrogen sulfide (H2S) has been recognized as a physiological mediator with a variety of functions across all domains of life. In this study, mechanisms of endogenous H2S generation in Shewanella oneidensis were investigated. As a research model with highly diverse anaerobic respiratory pathways, the microorganism is able to produce H2S by respiring on a variety of sulfur-containing compounds with SirACD and PsrABC enzymatic complexes, as well as through cysteine degradation with three enzymes, MdeA, SO_1095, and SseA. We showed that the SirACD and PsrABC complexes, which are predominantly, if not exclusively, responsible for H2S generation via respiration of sulfur species, do not interplay with each other. Strikingly, a screen for regulators controlling endogenous H2S generation by transposon mutagenesis identified global regulator Crp to be essential to all H2S-generating processes. In contrast, Fnr and Arc, two other global regulators that have a role in respiration, are dispensable in regulating H2S generation via respiration of sulfur species. Interestingly, Arc is involved in the H2S generation through cysteine degradation by repressing expression of the mdeA gene. We further showed that expression of the sirA and psrABC operons is subjected to direct regulation of Crp, but the mechanisms underlying the requirement of Crp for H2S generation through cysteine degradation remain elusive.